2014
DOI: 10.1007/s10995-014-1472-5
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Breastfeeding Initiation by Maternal Diabetes Status and Race, Ohio 2006–2011

Abstract: To examine breastfeeding trends at hospital discharge from 2006 to 2011 by diabetes status and to determine associations between diabetes status and breastfeeding. Ohio Vital Statistics birth certificate data from 2006 to 2011, including all singleton births to Ohio resident mothers of reproductive age (16-44 years), were used to analyze trends in breastfeeding by diabetes status [prepregnancy diabetes (PDM), gestational diabetes (GDM)]. Logistic regression was used to evaluate the relationship between breastf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 52 publications
0
29
0
Order By: Relevance
“…In the current study, within racial/ethnic groups of women, no differences in breastfeeding initiation were found between underweight and normal weight women. In contrast, Thompson et al 19 reported underweight non-Hispanic black and Hispanic women to be less likely to initiate breastfeeding compared with normal weight women, whereas Kachoria and Oza-Frank 27 reported underweight non-Hispanic white women were less likely to initiate breastfeeding than normal weight non-Hispanic white women. In Italy, researchers found that underweight women were less likely to initiate breastfeeding, but analyses did not include maternal race/ethnicity.…”
Section: Bmi and Breastfeeding By Race/ethnicitymentioning
confidence: 92%
See 4 more Smart Citations
“…In the current study, within racial/ethnic groups of women, no differences in breastfeeding initiation were found between underweight and normal weight women. In contrast, Thompson et al 19 reported underweight non-Hispanic black and Hispanic women to be less likely to initiate breastfeeding compared with normal weight women, whereas Kachoria and Oza-Frank 27 reported underweight non-Hispanic white women were less likely to initiate breastfeeding than normal weight non-Hispanic white women. In Italy, researchers found that underweight women were less likely to initiate breastfeeding, but analyses did not include maternal race/ethnicity.…”
Section: Bmi and Breastfeeding By Race/ethnicitymentioning
confidence: 92%
“…suggests some degree of directionality from prepregnancy BMI. Lastly, women who had multiple births were excluded from this study, but this deliberate restriction is consistent with the literature 15,17,19,27 and helps to control for possible confounding bias because women who give birth to multiples may face more challenges that in turn affect breastfeeding outcomes. 26…”
Section: Bmi and Breastfeeding By Race/ethnicitymentioning
confidence: 95%
See 3 more Smart Citations